Determining the dependability of Service-Oriented Architectures. (27th July 2007) - Looker, Nik; Xu, Jie; Munro, Malcolm
This paper introduces our novel method for the generation of fault injection test cases and failure detection by the use of our enhanced fault and failure models. Our enhanced fault model is an extension of a standard fault model that is constructed through decomposition to create a framework that facilitates automatic test generation. The failure model is based on a set of failure modes and again decomposed to create a framework to aid in the automatic detection of system failures. We demonstrate the Web Service-Fault Injection Technology (WS-FIT) method and fault injection tools with the use of some simulated real-world system.